Implementasi Keselamatan (K3) Terhadap Tenaga Kerja Pada Proyek Kontruksi Instalatur Pipa Gas Bumi PT. Multi Sinar Gemilang - Eko Wardiyanto; Chinta Yolanda Sari (Jurnal Anestesi, 2023)
Occupational Safety and Health (K3) is a very important program to be implemented by companies, especially companies engaged in construction. The purpose of this study is to investigate the occurrence of potential hazards of work accidents in natural gas pipeline installation projects in Mega Mall Batam. The method used in this research is survey distribution and project observation. The research findings state that there were incidents of work accidents in the natural gas pipeline installation project in Mega Mall Batam, namely workers who were hit by grinding stone splashes and workers who were crushed by one of the materials that fell from above the project. The implication of the research is that the company continues to improve the quality of K3 within PT. Multi Sinar Gemilang to reduce work accidents.